Intertemporal budget policies and macroeconomic adjustment in indebted open economies - Marcelo Bianconi; Walter H. Fisher (Institute for Advanced Studies (IHS), 2011)
We analyze the role of government intertemporal budget policies in a growing open economy including nominal assets in the presence of an upward sloping supply of debt. This introduces transitional dynamics that influence the effects of government policy instruments on the long term fiscal liability. In particular, shifts in capital income taxes can lead to dynamic scoring effects through the evolution of foreign debt. We show that a combination of tax-cum-expenditure, or government expenditure alone can balance the long term government budget constraint. However, for certain combinations of parameter values, the capital income tax alone cannot balance the intertemporal budget.
Keywords: E5; E6; F4; 330; government budget constraint; nominal assets; capital income tax